Clinical validation of controlled exposure to cat dander in the Specialized Particulate Control Environmental Exposure Unit (SPaC-EEU) - Lubnaa Hossenbaccus; Sophia Linton; Sarah Garvey; Hannah Botting; Terry Walker; Lisa Steacy; Anne K. Ellis (Allergy, Asthma & Clinical Immunology)
Abstract Background Cat allergen is the second most common cause of perennial allergic rhinitis. Despite its prevalence (~ 20% of the population), many patients continue to suffer from persistent symptoms due to constant exposure to cat allergens that reduce treatment efficacy. Modelling of the disease can improve our understanding of its onset and progression. The Specialized Particulate Control Environmental Exposure Unit (SPaC-EEU) is a controlled allergen challenge facility that has recently undergone a successful technical validation for cat dander exposure, measuring Felis domesticus 1 (Fel d 1). We then sought to perform a clinical validation with cat-allergic and non-allergic participants. Methods This study consisted of 3 visits. Recruited participants attended a Screening visit where eligibility was assessed, and a skin prick test (SPT) was completed. Successfully screened cat-allergic and non-allergic participants were invited back for the Allergen Exposure visit. They attended one of two 3-hour cat dander exposure Sessions in the SPaC-EEU, due to space limitations, with a target Fel d 1 concentration of 70 ng/m3. Fel d 1 concentrations were collected using air sampling cassettes and processed using a Fel d 1-specific ELISA. Real-time particle counts were monitored using a laser particle counter (LPC). Participants recorded symptom scores at time points from baseline up to 24 h post-onset of allergen exposure. Participants returned to the research site for a 24-hour Follow-up visit. Allergic participants completed a cat exposure and Quality of Life questionnaire. Results Forty-six (31 cat-allergic and 15 non-allergic) participants completed this study. Allergic participants had significantly larger (p < 0.0001) SPT wheals to cat hair than non-allergic controls. Twenty-five participants attended the first Session (mean Fel d 1 = 35.7 ng/m3), and 21 participants attended the second Session (mean Fel d 1 = 102.3 ng/m3). No significant differences in symptom and safety scores were observed between Sessions, hence participants’ data were pooled. Allergic participants experienced significantly elevated (p < 0.05) Total Nasal Symptom Scores and Total Rhinoconjunctivitis Symptom Scores from 15 min to 24-h post-onset of allergen exposure and significantly decreased (p < 0.05) percent change in Peak Nasal Inspiratory Flow from 1 to 3 hours, compared to non-allergic controls. Mean Quality of Life scores were different between phenotypes, unimpacted by whether or not one lived with a cat. Conclusion The SPaC-EEU can safely produce clinically relevant nasal symptoms in only cat-allergic participants, highlighting its use for modelling cat allergen-induced allergic rhinitis.